2009
DOI: 10.1186/1752-0509-3-96
|View full text |Cite
|
Sign up to set email alerts
|

The capacity for multistability in small gene regulatory networks

Abstract: Background: Recent years have seen a dramatic increase in the use of mathematical modeling to gain insight into gene regulatory network behavior across many different organisms. In particular, there has been considerable interest in using mathematical tools to understand how multistable regulatory networks may contribute to developmental processes such as cell fate determination. Indeed, such a network may subserve the formation of unicellular leaf hairs (trichomes) in the model plant Arabidopsis thaliana.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 61 publications
(66 reference statements)
1
37
0
Order By: Relevance
“…Although relatively little known within the biological sciences, Sturm's theorem has found applicability in a number of other areas where polynomials play an important role, including computational mathematics [25], dynamical systems [26,27], robotics [28] and finance [29]. Additional biological applications are possible, for example, as a tool to predict a large number of new bistable topologies or rule out those that do not have the capacity for bistability (such as chemical reaction network theory, previously [13,24]). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although relatively little known within the biological sciences, Sturm's theorem has found applicability in a number of other areas where polynomials play an important role, including computational mathematics [25], dynamical systems [26,27], robotics [28] and finance [29]. Additional biological applications are possible, for example, as a tool to predict a large number of new bistable topologies or rule out those that do not have the capacity for bistability (such as chemical reaction network theory, previously [13,24]). …”
Section: Discussionmentioning
confidence: 99%
“…The bistable regions (in a -g space) for these single gene circuits are shown in figure 2a. (The one-dimensional regions of bistability shown in bifurcation diagrams in [23,24] are plotted for comparison.) It can be seen that the l repressor circuit is bistable over a larger range and with lower values of the degradation rate constant.…”
Section: Bistable Single-gene Circuitsmentioning
confidence: 99%
“…We also derive sufficient conditions on the constant term of the characteristic polynomial to destabilize the equilibria. Our results are relevant because networks using exclusively monomeric repressors do not generally yield bistable behaviors [15], [16]. We conclude with numerical simulations which identify the region in parameter space where the system is bistable.…”
Section: Introductionmentioning
confidence: 73%
“…In these studies, it is found that a switch between the two stable states can be achieved by building a layer DNFL model or a cascade DNFL model [16][17][18][19][20][21][22] or by applying stimulation to the DNFL [23][24][25][26]8,27]. In some cases, an unresponsive switch could be necessary, and an unusually sensitive method could also be necessary to describe the ultrasensitization of the cellular signaling in other cases.…”
Section: Introductionmentioning
confidence: 99%